Stakeholders’ Views of Enclave Tourism: A Grounded Theory Approach - Nunkoo, R.; Ramkissoon, Haywantee (Sage Publications, 2016)
Using a grounded theory approach, this study investigates stakeholders’ views of enclave tourism in the island of Mauritius. In-depth interviews with tourism stakeholders were conducted and data were analyzed using the principles of grounded theory. Seven subthemes emerged from the analysis and these were categorized into two main themes: enclave tourism as an agent of empowerment/improvement and enclave tourism as a force of sociocultural destruction/denial of freedom. The themes suggest that stakeholders’ views are nuanced and often contradictory. In line with the principles of grounded theory, a conceptual framework explaining stakeholders’ views of enclave tourism is developed. The findings are discussed with existing literature and similarities and contradictions are noted. Unlike what is usually claimed by researchers and scholars, enclave tourism development results in some environmental and socioeconomic benefits, particularly with respect to sustainable hotel operations, empowerment of local community and women, and entrepreneurial opportunities.